Anthropological Perspective on the History of Religions Studies in the Republican Period - Tunc, Ismet; Kurt, Ali Osman (Şırnak Univ, 2020)
The studies on the history of religions in Turkey are fairly new. During the foundation years of the Republic, religion was one of the most emphasized subjects in general. The debates on religion have mostly been about the religion-state relationship and its impact on society. Although there are various opinions and evaluations on the subject, the idea that religion is a social necessity has been accepted and some studies have been done to put it on a legal basis. In this context, religious education followed a course that developed in the axis of nationalism. History of religions has also made its own path as a part of this course. In this study, the relationship between anthropology and the studies of the history of religions and their sources in Turkey are examined. The reflection of the relationship between the history of religions, which come to the fore in the field of theology, and anthropology, which is known as a secular science, on studies conducted to determine the cultural and religious phenomena in the first years of the Republic are discussed. In this context, it is important to understand the first occurrence of anthropology in Turkey and its role in building a nation-state. This study aims to reveal the reflections of the discussions and research made on religion and ethnographic data on the history of religions, obtained from Anatolia, and basic principles of the beginning of religious historiography in Turkey. This study is focused on a limited number of personalities and their works on the history of religion in the Republican period.
Keywords: History of Religions; Anthropology; Ethnography; Turkish Religious History; Hikmet Tanyu